Investigation of Monolingual German and Bilingual German–Persian Instruction Based on Vocabulary and Its Effect on Spoken Language - Boroumand Jazi , Bita; Mesgarzadeh Aghdam, Leili; Sahavi , Shahram (Assessment and Practice in Educational Sciences, 2025)
The issue of conducting foreign language classes based on monolingual or bilingual instruction is among the important topics in the field of education, which, in general, is examined in various countries. Vocabulary acquisition constitutes a significant part of language learning. Equating the target language with the same language leads to the expansion of the learner’s vocabulary range, resulting in mastery of spoken language and other skills mentioned in the study. The purpose of this research is to compare the teaching of a foreign language (German) in monolingual and bilingual formats in Iranian institutions, focusing on teacher-led instruction, and to examine its effect on the quality of learners’ language acquisition. A comparison of these cases at the intermediate level shows that, on average, a considerable proportion of learners in monolingual (German) settings are able to communicate fluently and confidently on various topics. Considering cultural aspects and engaging in discussions about the cultural issues of the target country and comparing them with those of the native country, through various texts, will lead to a deeper understanding and increased motivation among learners. One of the main objectives of this teaching method is to make foreign language classes conversation-oriented. One of the primary strategies to achieve this is instruction based entirely on the target language, independent of the native language, with automatic mental equivalence generation. Consequently, the broader the learner’s vocabulary range, the greater their gradual mastery of the target language will be, particularly in its spoken and written dimensions. Naturally, these results, consistent with the initial hypotheses, will have a significant impact on comprehension in various topics and situations